1998
DOI: 10.1128/mcb.18.11.6560
|View full text |Cite
|
Sign up to set email alerts
|

Global Regulatory Functions of Oaf1p and Pip2p (Oaf2p), Transcription Factors That Regulate Genes Encoding Peroxisomal Proteins in Saccharomyces cerevisiae

Abstract: Two transcription factors, Oaf1p and Pip2p (Oaf2p), are key components in the pathway by which several Saccharomyces cerevisiae genes encoding peroxisomal proteins are activated in the presence of a fatty acid such as oleate. By searching the S. cerevisiae genomic database for the consensus sequence that acts as a target for these transcription factors, we identified 40 genes that contain a putative Oaf1p-Pip2p binding site in their promoter region. Quantitative Northern analysis confirmed that the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 63 publications
10
141
1
Order By: Relevance
“…For an in-depth discussion of the applied statistics, see MATERIALS AND METH-ODS. The calculated mRNA levels from SAGE data obtained from glucose-grown and oleate-grown cells show good correlation with previously published data from Northern blotting experiments (Einerhand et al, 1991;Rottensteiner et al, 1996;Karpichev and Small, 1998). When genes were graphically displayed in order of decreasing tag frequency, a surprisingly small number of mRNAs were found to be present at high steady-state levels.…”
Section: Comparison Of Sage Tag Lists Determined For Glucose-grown Ansupporting
confidence: 67%
See 1 more Smart Citation
“…For an in-depth discussion of the applied statistics, see MATERIALS AND METH-ODS. The calculated mRNA levels from SAGE data obtained from glucose-grown and oleate-grown cells show good correlation with previously published data from Northern blotting experiments (Einerhand et al, 1991;Rottensteiner et al, 1996;Karpichev and Small, 1998). When genes were graphically displayed in order of decreasing tag frequency, a surprisingly small number of mRNAs were found to be present at high steady-state levels.…”
Section: Comparison Of Sage Tag Lists Determined For Glucose-grown Ansupporting
confidence: 67%
“…The peaks in Figure 1B alerted us to the genes that were highly expressed when cells were grown on oleate. A number of such genes were already known from previous work using Northern blotting and reporter gene studies (Einerhand et al, 1991;Rottensteiner et al, 1996;Karpichev and Small, 1998). Examples are genes encoding enzymes of the ā¤-oxidation pathway such as acyl-coenzyme A (CoA) oxidase (FOX1/POX1) and thiolase (FOX3/POT1) and other genes encoding peroxisomal matrix proteins such as catalase A (CTA1) and malate dehydrogenase isoform 3 (MDH3).…”
Section: Comparison Of Sage Tag Lists Determined For Glucose-grown Anmentioning
confidence: 99%
“…Numerous previous studies have shown oleate to cause a substantial induction in the size and/or number of Saccharomyces peroxisomes (Veenhuis et al 2003). Oleateinduced expression of PEX11 and the other PEX genes depends on Oaf1 and Pip2, transcription factors that bind as a heterodimer to the oleate-responsive element (Luo et al 1996;Rottensteiner et al 1996;Karpichev and Small 1998). Adr1, the transcription factor first identified as the inducer of yeast alcohol dehydrogenase (Ciriacy 1975), is also important for PEX gene induction (Simon et al 1991;Gurvitz et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Also, among the genes subject to the Cat8p control, several are significantly more expressed on oleate than on glucose. This is the case for ACS1, CAT2, CRC1, FBP1, ICL1, IDP2, JEN1, MDH2, MLS1, PCK1, PUT4, SFC1, and YCR010C (29,30). This finding illustrates the relationships between different pathways involved in the switch to alternative carbon sources.…”
Section: Regulation Of the Expression Of The Cat8p-dependent Genes-mentioning
confidence: 99%